2021
DOI: 10.1111/1744-7917.12963
|View full text |Cite
|
Sign up to set email alerts
|

Validamycin treatment significantly inhibits the glycometabolism and chitin synthesis in the common cutworm,Spodoptera litura

Abstract: Validamycin, as a broadly applied antibiotic, has been used to control rice sheath blight disease. Furthermore, validamycin was considered as an insecticide to control agricultural pests. Insight into the mechanism of validamycin's action on insects can provide molecular targets for the control of agricultural pests. In this study, a toxicological test analysis revealed that Spodoptera litura larval growth and development was significantly inhibited and the pupation rate was significantly reduced with the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Inhibition of the VgR expression can cause Vg to be deposited in large amounts in the hemolymph. This prevents its smooth entry into the ovaries, ultimately hindering ovarian tube development and significantly reducing egg production [48,57]. The prevention of a normal egg output by blackened and clumped egg and mating sacs in the fallopian tubes may have been a major reason for the decrease in egg production.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the VgR expression can cause Vg to be deposited in large amounts in the hemolymph. This prevents its smooth entry into the ovaries, ultimately hindering ovarian tube development and significantly reducing egg production [48,57]. The prevention of a normal egg output by blackened and clumped egg and mating sacs in the fallopian tubes may have been a major reason for the decrease in egg production.…”
Section: Discussionmentioning
confidence: 99%
“…Validamycin has been demonstrated to be a very strong inhibitor against trehalase in a variety of organisms, such as insects, nematodes, and fungi, and thus has raised plenty of interest in recent years [ 45 , 46 , 47 ]. As a matter of fact, validamycin has long been used as an anti-fungal agricultural antibiotic to control rice sheath blight due to its superior property of high efficiency and environmental friendliness [ 48 ]. Currently, although validamycin is not commonly used for managing insect pests, a large body of evidence has pointed out the potential feasibility in this field.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, although validamycin is not commonly used for managing insect pests, a large body of evidence has pointed out the potential feasibility in this field. For example, a toxicological test analysis revealed that Spodoptera litura (Lepidoptera: Noctuidae) larval growth and development was significantly inhibited and the pupation rate was significantly reduced after validamycin treatment [ 48 ]. In addition, validamycin treatment significantly increased the mortality rate of Diaphorina citri adult insects, reduced the pupation rate, and caused significant deformities in adult insects [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As an important energy substance in the hemolymph of insects, trehalose metabolism is beneficial to the development of oocytes and participates in the uptake of Vg by oocytes (Santos et al 2008, Wang et al 2020). Trehalase (TRE) is the only enzyme known to break down trehalose in all organisms participating in the energy metabolism process of the organism and regulating physiological processes such as development and reproduction, molting, and metamorphosis (Elbein et al 2003, Tang et al 2018, Wang et al2021, Yu et al 2022). Inhibition of trehalose metabolism causes delayed ovarian development and abnormal oogenesis in Bombyx mori (Katagiri et al 1998).…”
Section: Introductionmentioning
confidence: 99%